Immunogenicity, Effectiveness, and Safety of COVID-19 Vaccines among Patients with Immune-Mediated Dermatological Diseases: A Systematic Review and Meta-analysis - Sonphet Chirasuthat; Yanisa Ratanapokasatit; Kunlawat Thadanipon; Kumutnart Chanprapaph (Medical Journals Sweden, 2024)
Immunocompromised individuals, primarily attributable to using immunosuppressants, face heightened COVID-19 risks. Despite the proven efficacy of COVID-19 vaccines, their impact on patients with immune-mediated dermatological diseases remains unclear. This study aims to thoroughly examine vaccine immunogenicity, effectiveness, and safety in immune-mediated dermatological disease patients. Clinical studies in adults that compared vaccinated immune-mediated dermatological disease patients with vaccinated healthy controls or unvaccinated immune-mediated dermatological disease patients in terms of vaccine immunogenicity, COVID-19 infection, adverse events, or exacerbation of immune-mediated dermatological diseases were searched via electronic databases. Seventeen studies (1,348,690 participants) were included. Seroconversion rates between immune-mediated dermatological disease patients and healthy controls were not different. However, among individuals aged ≤55 years, immune-mediated dermatological disease patients had lower mean anti-SARS-CoV-2 IgG levels. Immunosuppressed immune-mediated dermatological disease patients also had lower titres and were less likely to achieve T-cell response. In terms of safety, the risk of adverse events was higher in atopic dermatitis patients, but those with psoriasis had a reduced risk. Additionally, immunosuppressed patients had fewer adverse events. Vaccinated immune-mediated dermatological disease patients had a lower risk of COVID-19 infection than unvaccinated patients but a higher risk than healthy controls; however, disease exacerbation may be induced. In conclusion, immune-mediated dermatological diseases showed a reduced vaccine response in our meta-analysis, yet vaccination remained effective against COVID-19 infection and well tolerated.